Optimization of growth of Levilactobacillus brevis SP 48 and in vitro evaluation of the effect of viable cells and high molecular weight potential postbiotics on Helicobacter pylori - Cimini, Donatella; D’ambrosio, Sergio; Stellavato, Antonietta; Fusco, Alessandra; Corsaro, Maria Michela; Dabous, Azza; Casillo, Angela; Donnarumma, Giovanna; Giori, Andrea Maria; Schiraldi, Chiara (Frontiers in Bioengineering and Biotechnology, 2022)
Several Levilactobacillus brevis strains have the potential to be used as probiotics since they provide health benefits due to the interaction of live cells, and of their secreted products, with the host (tissues). Therefore, the development of simple fermentation processes that improve cell viability to reduce industrial production costs, and at the same time the characterization and biological evaluation of cell-free postbiotics that can further promote application, are of great interest. In the present study, small scale batch fermentations on semi defined media, deprived of animal derived raw materials, were used to optimize growth of L. brevis CSL, reaching 1.2±0.4x1010 CFU/mL of viable cells after 16h of growth. Displacement, competition, and inhibition assays compared the effect, on Helicobacter pylori, of L. brevis cells to that of its partially purified postbiotic fraction rich in exopolysaccharides and proteins. The expression of pro and anti-inflammatory biochemical markers indicated that both samples activated antimicrobial defenses and innate immunity in a gastric model. Moreover, the postbiotic fraction also acted as modulator of the inflammatory response in a gut in vitro model. These data demonstrate that the high molecular weight compounds secreted by L. brevis can contrast H. pylori and reduce inflammation related to intestinal bowel disease, potentially overcoming issues related to the preservation of probiotic viability.